19.7k views
0 votes
PLEASEEEEE HELPPP MEEE WITHH THIS QUESTIONN PLEASEEE

PLEASEEEEE HELPPP MEEE WITHH THIS QUESTIONN PLEASEEE-example-1
User Mazen
by
5.5k points

1 Answer

3 votes

Answer: A

Explanation:

To find the average rate of change, you use the formula
(f(b)-f(a))/(b-a). The best way to get the correct answer is to plug in each interval to make sure it equals 0.

-1 ≤ x ≤ 2: Correct


(f(2)-f(-1))/(2-(-1)) [solve for f(2) and f(1)]


(1-1)/(3)=(0)/(3) =0

------------------------------------------------------------------------------------------------------

-3 ≤ x ≤ -2: Incorrect


(f(-2)-f(-3))/(-2-(-3)) [solve for f(-2) and f(-3)]


(5-11)/(1) =(-6)/(1)=-6

------------------------------------------------------------------------------------------------------

-5 ≤ x ≤ 5: Incorrect


(f(5)-f(-5))/(5-(-5)) [solve for f(5) and f(-5)]


(19-29)/(10) =(-10)/(10) =-1

------------------------------------------------------------------------------------------------------

2 ≤ x ≤ 3: Incorrect


(f(3)-f(2))/(3-2) [solve for f(3) and f(2)]


(5-1)/(1) =(4)/(1) =4

------------------------------------------------------------------------------------------------------

After going through all the intervals, we found that A was the only one that has an average rate of change of 0.

User Cabrera
by
4.7k points